2020
DOI: 10.3389/fneur.2020.578588
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using the Video-Head Impulse Test to Detect the Involved Canal in Benign Paroxysmal Positional Vertigo Presenting With Positional Downbeat Nystagmus

Abstract: Positional downbeat nystagmus (pDBN) represents a relatively frequent finding. Its possible peripheral origin has been widely ascertained. Nevertheless, distinguishing features of peripheral positional nystagmus, including latency, paroxysm and torsional components, may be missing, resulting in challenging differential diagnosis with central pDBN. Moreover, in case of benign paroxysmal positional vertigo (BPPV), detection of the affected canal may be challenging as involvement of the non-ampullary arm of poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 92 publications
1
27
1
Order By: Relevance
“…Although a reverse functional dissociation pattern impairing low-velocity while sparing high-velocity canal VOR has been often observed in several vestibular diseases ( 66 – 69 ), other vestibular pathologies have been related to a loss of sensitivity for high-acceleration head movements while low-acceleration behavior remains intact, likewise LF herein reported ( 70 – 72 ). In particular, SSC dehiscence represents another condition accounting for a third window mechanism that has been demonstrated to result in ocular movements aligning with the plane of the affected canal in response to loud sounds and/or pressure changes despite selectively impaired canal function on vHIT.…”
Section: Discussionsupporting
confidence: 56%
“…Although a reverse functional dissociation pattern impairing low-velocity while sparing high-velocity canal VOR has been often observed in several vestibular diseases ( 66 – 69 ), other vestibular pathologies have been related to a loss of sensitivity for high-acceleration head movements while low-acceleration behavior remains intact, likewise LF herein reported ( 70 – 72 ). In particular, SSC dehiscence represents another condition accounting for a third window mechanism that has been demonstrated to result in ocular movements aligning with the plane of the affected canal in response to loud sounds and/or pressure changes despite selectively impaired canal function on vHIT.…”
Section: Discussionsupporting
confidence: 56%
“…A partial canal jam might determine impaired responses for high-frequency stimuli, such as head impulses in v-HIT, whereas low-frequency stimuli, such as the cupular stimulus of the endolymph flow activated during the positional test, remain active (low-pass filter). Data reported by Castellucci et al 23 highlight the difference between APC and TPC, in which the posterior canal VOR gain is not affected 24 .…”
Section: Discussionmentioning
confidence: 85%
“…In a recent multicentre study through v-HIT, Castellucci et al 23 demonstrated a decrease of the VOR gain of the affected canal in 72.9% of 59 cases of PDN, either from APC or from AC, increasing up to 88.6% in the subgroup with persistent down beat nystagmus, either positional or spontaneous. This datum was useful to distinguish between APC and contralateral AC.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, we would also suggest to always warrant further investigations for patients presenting with isolated loss of SSC function on vHIT, as SCD might not be the sole underlying disorder as it has been found among 300 patients in a recently published study [7]. In fact, along with anecdotal reports implicating Meniere's disease in the acute stage [20], Castellucci et al have reported how benign positional paroxysmal vertigo (BPPV) presenting with positional downbeat nystagmus due to an involvement of a vertical canal might lead to a selective impairment of the affected canal VOR- gain, including the SSC [16,17]. Probably, the unlikelihood to examine patients either during the acute attack of Meniere's disease or with SSC-BPPV (accounting for less than 10% of overall BPPV) could represent one of the reasons for this discrepancy.…”
Section: Inner Ear Disorders Accounting For Isolated Impairment Of Scmentioning
confidence: 97%
“…In fact, it has been reported how Tullio phenomenon does not only arise from a sustained triggering of phaselocking irregularly-discharging sensors, but also to a slowly developing but sustained activation of regularly discharging afferents [4,15]. Similarly, cases with persistent positional downbeat nystagmus, where an incomplete canal plug (also called "incomplete canalith jam") exerted by an otolith clot has been assumed as the underlying mechanism, have also been related to the same functional dissociation paradigm impairing high-velocity responses while sparing low-velocity VOR for the canal involved [16,17].…”
Section: Incomplete Canal Pluggingmentioning
confidence: 99%